PROBLEMATIKA PENGGUNAAN RAGAM BAHASA JURNALISTIK PADA MEDIA MASSA DAN IMPLIKASINYA TERHADAP PEMBINAAN BAHASA INDONESIA DI MASYARAKAT - Marliana, N Lia; Puryanto, Edi (Diksi, 2015)
Good print media are those prioritizing the writing quality. Although they emphasize more on effectiveness, efficiency, and cost, they should take into account of the writing quality, without violating the Indonesian language rules. Some violations found in journalistic writing include: (1) spelling and punctuation violations, (2) grammatical violations, consisting of errors in syllable separation, morphological violations, and syntactic errors, (3) semantic violations, and (4) discourse violations. Other problems concern loanwords, namely foreign words that are already popular in the community. The replacement of foreign words absorbed into the Indonesian language with unavailable Indonesian equivalents results in difficulty. Keywords: journalistic language, mass media, language maintenance